A randomized controlled clinical study on Zuo's acupuncture treatment for prediabetes. Issue 8 (25th February 2022) - Zeng, Xuanli; Li, Yang; Lu, Liming; Wen, Hao; Wang, Guorui; Zuo, Changbo
Abstract: Introduction: Prediabetes is a high-risk stage of transition to type 2 diabetes mellitus. Previous studies suggest that acupuncture has potential to prevent prediabetes' conversion to type 2 diabetes mellitus, which lack of high-quality evidence. Zuo's acupuncture, a kind of acupuncture technique, is formed through long-term and repeated clinical practice by professor Zuo Changbo who integrates the internal meaning of Dong extra acupoints and Taoist medicine principle according to the theories of traditional Chinese medicine. It is used clinically to increase the regression toward normo-glycemi on prediabetes. The objective of this trial is to clarify the clinical effectiveness and safety of Zuo acupuncture for prediabetes. Methods and analysis: This study is a prospective randomized controlled trial in which 60 patients with prediabetes will be randomly allocated in a 1:1 ratio into either an acupuncture treatment group or a control group. Prediabetes patients in the control group will receive prediabetes health education for lifestyle interventions, whereas patients in the acupuncture group will receive lifestyle interventions plus Zuo Daliji and Yueku stitch treatment. Twenty-four treatment sessions will be performed over 3 months. The primary outcome is conversion rate from prediabetes to normal blood glucose. Secondary outcomes include fasting plasma glucose, 2-hour plasma glucose, glycosylated hemoglobin and blood lipid concentration. Ethics and dissemination: This study was approved by the Ethics Committee of Guangdong Provincial Hospital of Chinese Medicine (permission number: YF2020-107-01) and the protocol conforms to the principles of the Declaration of Helsinki. Data collection will be completed by June 2022. Publications will be ready for submission in July 2022.